Allele- and Tir-Independent Functions of Intimin in Diverse Animal Infection Models - Mallick, Emily M.; Brady, Michael J.; Luperchio, Steven A.; Vanguri, Vijay; Magoun, Loranne; Liu, Hui; Sheppard, Barbara J.; Mukherjee, Jean; Donohue-Rolfe, Arthur; Tzipori, Saul; Leong, John M.; Schauer, David B. (Frontiers in Microbiology, 2012)
Upon binding to intestinal epithelial cells, enterohemorrhagic E. coli (EHEC), enteropathogenic E. coli (EPEC), and Citrobacter rodentium trigger formation of actin pedestals beneath bound bacteria. Pedestal formation has been associated with enhanced colonization, and requires intimin, an adhesin that binds to the bacterial effector Tir, which is translocated to the host cell membrane and promotes bacterial adherence and pedestal formation. Intimin has been suggested to also promote cell adhesion by binding one or more host receptors, and allelic differences in intimin have been associated with differences in tissue and host specificity. We assessed the function of EHEC, EPEC, or C. rodentium intimin, or a set of intimin derivatives with varying Tir-binding abilities in animal models of infection. We found that EPEC and EHEC intimin were functionally indistinguishable during infection of gnotobiotic piglets by EHEC, and that EPEC, EHEC, and C. rodentium intimin were functionally indistinguishable during infection of C57BL/6 mice by C. rodentium. A derivative of EHEC intimin that bound Tir but did not promote robust pedestal formation on cultured cells was unable to promote C. rodentium colonization of conventional mice, indicating that the ability to trigger actin assembly, not simply to bind Tir, is required for intimin-mediated intestinal colonization. Interestingly, streptomycin pre-treatment of mice eliminated the requirement for Tir but not intimin during colonization, and intimin derivatives that were defective in Tir-binding still promoted colonization of these mice. These results indicate that EPEC, EHEC, and C. rodentium are functionally interchangeable during infection of gnotobiotic piglets or conventional C57BL/6 mice, and that whereas the ability to trigger Tir-mediated pedestal formation is essential for colonization of conventional mice, intimin provides a Tir-independent activity during colonization of streptomycin pre-treated mice.